2017
DOI: 10.1002/2016wr019656
|View full text |Cite
|
Sign up to set email alerts
|

Improved modeling of snow and glacier melting by a progressive two‐stage calibration strategy with GRACE and multisource data: How snow and glacier meltwater contributes to the runoff of the Upper Brahmaputra River basin?

Abstract: Snow and glacier melting and accumulation are important processes of the hydrological cycle in the cryosphere, e.g., high‐mountain areas. Glaciers and snow cover respond to climate change notably over the Tibetan Plateau (TP) as the Earth's Third Pole where complex topography and lack of ground‐based observations result in knowledge gaps in hydrological processes and large uncertainties in model output. This study develops a snow and glacier melt model for a distributed hydrological model (Coupled Routing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 107 publications
(177 reference statements)
8
112
0
Order By: Relevance
“…The GLDAS 2.1 soil moisture, which had been validated using observations (Figure S4), was used because the observations were only up to 2010. Snow and glacier are important factors for the hydrological cycle in high‐mountain cryosphere (Chen et al, ), for example, the headwaters of the Yellow River. The north Tibetan Plateau, where the Yellow River originates, was found to show a significant increasing trend in TWSA by Long et al (), and the increase was mainly attributed to lake expansion from increased precipitation and glacier melting.…”
Section: Resultsmentioning
confidence: 99%
“…The GLDAS 2.1 soil moisture, which had been validated using observations (Figure S4), was used because the observations were only up to 2010. Snow and glacier are important factors for the hydrological cycle in high‐mountain cryosphere (Chen et al, ), for example, the headwaters of the Yellow River. The north Tibetan Plateau, where the Yellow River originates, was found to show a significant increasing trend in TWSA by Long et al (), and the increase was mainly attributed to lake expansion from increased precipitation and glacier melting.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their global coverage and independence from surface conditions, the data represent a unique opportunity to quantify spatio-temporal variations of the Earth's water resources (Alkama et al, 2010;Werth et al, 2009). Therefore, GRACE data have been widely used to diagnose patterns of hydrological variability (Seo et al, 2010;Rodell et al, 2009;Ramillien et al, 2006;Feng et al, 2013), to validate and improve model simulations Güntner, 2008;Werth and Güntner, 2010;Chen et al, 2017;Eicker et al, 2014;Girotto et al, 2016;Schellekens et al, 2017), and to enhance our understanding of the water cycle on regional to global scales (Syed et al, 2009;Felfelani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few models used to assess hydrological processes on continental to global scales are constrained by observations, and if so, they are mainly calibrated against the observed discharge of large river basins (Long et al, 2015;Döll et al, 2015). Recently, several studies showed the benefits of additionally including GRACE TWS data in model calibration (Werth and Güntner, 2010;Xie et al, 2012;Chen et al, 2017) or by means of data assimilation Forman et al, 2012;Kumar et al, 2016). However, although these approaches improve model simulations, they do not reduce the uncertainty in the partitioning of TWS due to the parameter equifinality problem (Güntner, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other midlatitude regions, seasonal snow cover over the TP has unique features in terms of global snow cover map because of the high mountains and it has vital water storage properties [ Pu et al ., ]. With an accelerated change in the environment on the TP caused by climate change [ Zhong et al ., ], including anomalies in warming trend [ Duan and Xiao , ], advanced vegetation green‐up dates [ Zhang et al ., ], enhanced evaporative cooling [ Shen et al ., ], and shrinking glaciers [ Chen et al ., ; Long et al ., ; Yao et al ., ] in most regions over the TP, the status of snow cover and its contribution to the Earth climate system remain unknown.…”
Section: Introductionmentioning
confidence: 99%